What to Expect When the Unexpected Becomes Expected: Harmonic Surprise and Preference Over Time in Popular Music - Miles, Scott A.; Rosen, David S.; Barry, Shaun; Grunberg, David; Grzywacz, Norberto (Frontiers in Human Neuroscience, 2021)
Previous work demonstrated that music with more surprising chords tended to be perceived as more enjoyable than music with more conventional harmonic structures. In that work, harmonic surprise was computed based upon a static distribution of chords. This would assume that zeroth-order harmonic surprise is constant over time, and the effect of harmonic surprise on music preference is similarly static. In this study we assess that assumption and establish that the relationship between harmonic surprise (as measured according to a specific time period) and music preference is not constant as time goes on. Analyses of harmonic surprise and preference from 1958-1991 showed increased harmonic surprise over time, and that this increase was significantly more pronounced in preferred songs. Separate analyses showed similar increases over the years from 2000-2019. As such, these findings provide evidence that the human perception of tonality is influenced by exposure. Baseline harmonic expectations that were developed through listening to the music of "yesterday" are violated in the music of "today'', leading to preference. Then, once the music of "today" provides the baseline expectations for the music of "tomorrow", more pronounced violations -- and with them, higher harmonic surprise values -- become associated with preference formation. We call this phenomenon the "Inflationary-Surprise Hypothesis". Support for this hypothesis could impact the understanding of how the perception of tonality, and other statistical regularities, are developed in the human brain.